A Precise GNSS Kinematic Observation Using Absolute Positioning Method at Bandar Universiti Residential Area: The precision of GNSS Kinematic Observation by using Absolute Positioning Method - Kassim, Muhammad Khairuddin (Recent Trends in Civil Engineering and Built Environment, 2021)
Absolute Positioning (AP) mode, related to pseudo-range measurements, limits the level of accuracy to several meters in open sky and to several dozens of meters in urban canyons. This study explores the effect of using a large number of Absolute Positioning(AP) observations from Leica Viva GS10/GS15 receivers. Data segmentation and bootstrapping statistical methods were used to obtain the deviation, which can describe the accuracy of the large sample. The final goal was to obtain the single positioning and associated deviations from single GNSS receivers positioned on a network. The process was tested in two geodetic network examples. The results indicated that the enhanced Absolute Positioning mode was able to improve its accuracy. Errors of several meters were reduced to values close to 50 cm in 25–37 min periods. For all observations from multiple GNSS systems, a closely coupled observational model assumes a single difference satellite. Investigation on the influence of different frequencies on Absolute Positioning (AP) and the development of precise accuracy can be improved with both code and carrier phase can be use together with Precise Point Positioning that allows certain errors to be eliminated.